Palatal Soft Tissue Thickness on Maxillary Posterior Teeth and Its Relation to Palatal Vault Angle Measured by Cone-Beam Computed Tomography - Doosadee Hormdee; Thanwarat Yamsuk; Pipop Sutthiprapaporn (Hindawi Limited, 2020)
Objective. Analyzing palatal soft tissue thickness in cone-beam computed tomography (CBCT) images and evaluating the relationship between tissue thickness and palatal vault angulation. Methods. Out of 1,737 CBCT images, fifty-six images met the inclusion criteria and were included in this cross-sectional study. The palatal vault angle on the maxillary first molar was measured and divided the images into 3 groups. The soft tissue thickness between the maxillary first premolar and second molar was measured at a distance of 3, 6, 7, 8, and 9 mm from the cementoenamel junction. All the image measurements were performed using CBCT-viewer software. Result. In this study, 56 CBCT images with full permanent maxillary posterior teeth and absence of light scattering were found. The mean age of the patients was 31.59 ± 13.92 years. The moderate and deep palatal vault angle patterns had the greatest and least prevalence, respectively. The average thickness on shallow, moderate, and deep palatal vault groups was 4.02 ± 0.58, 3.75 ± 0.73, and 3.43 ± 0.38 mm, respectively. Furthermore, the mean palatal mucosal thickness was statistically different between the deep and shallow palatal vault angle groups (p<0.05, power of test 0.8). Based on the Pearson correlation coefficient, there was a negative correlation between the palatal mucosal thickness and palatal vault angle (p<0.05, power of test 0.85). Conclusion. A negative correlation between the palatal mucosal thickness and palatal vault angle was observed. Furthermore, this study suggested that the shape of the palatal vault can be one of the supporting data for evaluating the graft dimensions.